2011
DOI: 10.31018/jans.v3i2.183
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity evaluation of pesticide profenofos by applying dominant lethal test on Culex quinquefasciatus

Abstract: Abstract:The present paper deals with the genotoxicity evaluation of profenofos by applying dominant lethal test (DLT) on Culex quinquefasciatus taken as an experimental model. For this, the males hatched from the larvae treated with LC 20 of pesticide were crossmated with normal females and the results were based on the number of hatched and unhatched eggs laid by these females. Mean percentage frequency of unhatched eggs was as low as 3.97 in the normal stocks as compared to treated stocks in which the frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…And caused killed Culex pipiens larvae and AChE was inhibition. (Bhinder and Chaudhry 2013) the toxicity of pesticides acephate and chlorpyrifos on Culex quinquefasciatus. Inhibited un-hatched eggs.…”
Section: Effect Of Diflubenzuron Inhibitormentioning
confidence: 99%
See 1 more Smart Citation
“…And caused killed Culex pipiens larvae and AChE was inhibition. (Bhinder and Chaudhry 2013) the toxicity of pesticides acephate and chlorpyrifos on Culex quinquefasciatus. Inhibited un-hatched eggs.…”
Section: Effect Of Diflubenzuron Inhibitormentioning
confidence: 99%
“…Alout et al, (2012) found that pyrimidine Trione Furan-substituted (PTF) compounds tested on mosquito and caused killed Culex pipiens larvae and AChE was inhibition. Bhinder and Chaudhry (2013) the toxicity of pesticides acephate and chlorpyrifos on Culex quinquefasciatus inhibited unhatched eggs. Masarrat et al, (2014) control mosquito Culex fatigans using lambdacyhalothrin, chlorpyrifos were significant efficacy against Cx.…”
Section: Introductionmentioning
confidence: 99%